Influência de Dendrocephalus brasiliensis Pesta, 1921 (Crustacea: Anostraca) na dinâmica da comunidade planctônica em três lagoas temporárias do município de Urucuia, MG - Passos, Rodrigo Ferroni (Universidade Federal de São Carlos, 2012)
Ecological short-term studies were conducted in three temporary ponds where naturally occurs the fairy shrimp Dendrocephalus brasiliensis, focusing mainly on structure and dynamics of zooplankton. These ponds are located at Minas Gerais State, Brazil. Samples were collected just after the rainy season of 2011, during seven consecutive days in the two first ponds (P1 and P2) and six days in the third pond (P3). The three environments were shallow and showed high temperatures during the sampling period. Were also determined the concentrations of nutrients, suspended material and chlorophyll a in the water in the studied environments. The values of these variables increased after heavy rain. Qualitative and quantitative analyses of zooplankton community showed low richness in these ponds and diversity indices are specially related to rain. Number and relative abundance of zooplankton groups were related to the presence and density of D. brasiliensis. Analysis of phytoplankton and chlorophyll a showed that ponds with higher phytoplankton density seem to be favorable for some zooplankton groups such as rotifers and of D. brasiliensis. High densities of D. brasiliensis cysts in the sediments of the temporary ponds studied indicate that this species is well established in these environments. The CCA and Monte Carlo analyses demonstrate that most of the zooplankton community in the three temporary ponds were related with variable chlorophyll a.
Keywords: Limnologia; Crustáceo; Comunidade planctônica; Zooplâncton; Anostraca; CIENCIAS BIOLOGICAS::ECOLOGIA